Microcontroller-based Bird Pest Repellent in Rice Plants - Nonik Silvia Agustin; Koko Joni; Diana Rahmawati; Adi Kurniawan Saputro (Procedia of Engineering and Life Science, 2021)
In the cultivation of rice, there is never a problem with the name pests. If not controlled, the pest attack will affect the productivity level of the plant. Pests that attack rice plants include leafhoppers and birds. Birds have a very large percentage rate in attacking rice plants, namely the bondol bird which is one of the grain-eating birds. This bird is a very troubling pest for rice farmers because it causes crop yields to drop dramatically. There are several ways to repel birds, usually farmers using the manual method by making a rice field and crackle which is then tied to a rope. When using this method, farmers have to wait for agricultural land for approximately one month. This is considered inefficient considering the farmer's job is not only to wait for the rice plant until harvesting. So that in this study, a tool that will be used to repel bird pests will be designed by using solar panels as a source of voltage with sound output using a frequency of 1.5 - 3 KHz.